Influence of Light on Particulate Organic Matter Utilization by Attached and Free-Living Marine Bacteria - Gómez-Consarnau, Laura; Needham, David M.; Weber, Peter K.; Fuhrman, Jed A.; Mayali, Xavier (Frontiers in Microbiology, 2019)
Light plays a central role on primary productivity of aquatic systems. Yet, its potential impact on the degradation of photosynthetically-produced biomass is not well understood. We investigated the patterns of light-induced particle breakdown and bacterial assimilation of detrital C and N using 13C and 15N labeled freeze-thawed diatom cells incubated in laboratory microcosms with a marine microbial community freshly-collected from the Pacific Ocean. Particles incubated in the dark resulted in increased bacterial counts and dissolved organic carbon concentrations compared to those incubated in the light. Light also influenced the attached and free-living microbial community structure as detected by 16S rRNA gene amplicon sequencing. For example, Sphingobacteriia were enriched on dark-incubated particles and taxa from the family Flavobacteriaceae and the genus Pseudoalteromonas were numerically enriched on particles in the light. Isotope incorporation analysis by phylogenetic microarray and NanoSIMS (a method called Chip-SIP) identified free-living and attached microbial taxa able to incorporate N and C from the particles. Some taxa, including members of the Flavobacteriaceae and Cryomorphaceae, exhibited increased isotope incorporation in the light, suggesting the use of photoheterotrophic metabolisms. In contrast, some members of Oceanospirillales and Rhodospirillales showed decreased isotope incorporation in the light, suggesting that their heterotrophic metabolism, particularly when occurring on particles, might increase at night or may be inhibited by sunlight. These results show that light influences particle degradation and C and N incorporation by attached bacteria, suggesting that the transfer between particulate and free-living phases are likely affected by external factors that change with the light regime, such as time of day, depth and season.